Low-Temperature Ionizing Radiation Resistance of Deinococcus radiodurans and Antarctic Dry Valley Bacteria - Dartnell, LR; Hunter, SJ; Lovell, KV; Coates, AJ; Ward, JM (MARY ANN LIEBERT INC, 2010)
The high flux of cosmic rays onto the unshielded surface of Mars poses a significant hazard to the survival of martian microbial life. Here, we determined the survival responses of several bacterial strains to ionizing radiation exposure while frozen at a low temperature characteristic of the martian near-subsurface. Novel psychrotolerant bacterial strains were isolated from the Antarctic Dry Valleys, an environmental analogue of the martian surface, and identified by 16S rRNA gene phylogeny as representatives of Brevundimonas, Rhodococcus, and Pseudomonas genera. These isolates, in addition to the known radioresistant extremophile Deinococcus radiodurans, were exposed to gamma rays while frozen on dry ice (-79 degrees C). We found D. radiodurans to exhibit far greater radiation resistance when irradiated at -79 degrees C than was observed in similar studies performed at higher temperatures. This greater radiation resistance has important implications for the estimation of potential survival times of microorganisms near the martian surface. Furthermore, the most radiation resistant of these Dry Valley isolates, Brevundimonas sp. MV.7, was found to show 99% 16S rRNA gene similarity to contaminant bacteria discovered in clean rooms at both Kennedy and Johnson Space Centers and so is of prime concern to efforts in the planetary protection of Mars from our lander probes. Results from this experimental irradiation, combined with previous radiation modeling, indicate that Brevundimonas sp. MV.7 emplaced only 30 cm deep in martian dust could survive the cosmic radiation for up to 100,000 years before suffering 10(6) population reduction.